Modified magnesium oxide cold-pressing adhesive, preparation method thereof, flame-retardant plywood and manufacturing method of flame-retardant plywood

By introducing a cellulose cross-linked polyacrylamide hydrogel network into magnesium oxide cement-based cold pressing glue, a liquid-solid phase two-component glue system is formed, which solves the problems of low viscosity, short opening time and hygroscopic corrosion of cold pressing glue, and achieves higher bonding effect, heat resistance, water resistance and corrosion resistance.

CN119875519APending Publication Date: 2025-04-25TREEZO NEW MATERIAL TECH GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510097166.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing magnesium oxide cement-based cold pressing glue has low viscosity and short opening time, which easily absorbs moisture and leads to ion precipitation and corrosion of steel nails/keels, and its performance is not close to that of the existing urea glue.

Method used

Cellulose cross-linked polyacrylamide is used to construct a hydrogel network to form a two-component glue system of liquid-phase glued components and solid-phase glued components, improving the bonding effect and opening time, and reducing the impact of frost and hygroscopicity.

Benefits of technology

It improves the viscosity, compactness and fluidity of cold pressed glue, extends the opening time, reduces frost and moisture absorption problems, enhances the heat and water resistance of the glue layer, and avoids free ions corrosion of the metal structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875519A_ABST
    Figure CN119875519A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives for artificial boards, and particularly discloses a modified magnesium oxide cold-pressing adhesive and a preparation method thereof. According to the modified magnesium oxide cold-pressing adhesive, cellulose-polyacrylamide hydrogel is mainly added on the basis of an existing magnesium oxide adhesive, a hydrogel network constructed by cellulose cross-linking polyacrylamide and a magnesium oxide adhesive basic system form an interpenetrating network, the stability of a liquid-phase gluing component is guaranteed, and the performance of the magnesium oxide cold-pressing adhesive is improved. The viscosity, the compactness and the flowability of an inorganic gel system are improved, the coating thickness and the mechanical property of an adhesive layer are ensured, and the permeability is reduced; the opening time can be obviously prolonged, and the requirement of the process on time is met; the temperature-sensitive cellulose-polyacrylamide hydrogel can also play a role in anchoring ions, so that the adverse effects of scumming, moisture absorption and the like are reduced, and free ions in the hydrogel are prevented from corroding metal structures such as keels and the like during application. The invention further discloses flame-retardant plywood based on the modified magnesium oxide cold-pressing adhesive and a manufacturing method of the flame-retardant plywood.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives for artificial boards, and in particular relates to a modified magnesium oxide cold-pressed adhesive and a preparation method thereof, as well as a flame-retardant plywood based on the modified magnesium oxide cold-pressed adhesive and a production method thereof. Background Art

[0002] Formaldehyde release and flammability are the two major pain points of artificial boards. Inorganic plywood has the advantages of being formaldehyde-free, flame retardant, mildew-proof, anti-corrosion, waterproof and moisture-resistant. At the same time, it adopts a cold pressing and curing process, and has the advantages of low production energy consumption and high board surface flatness. It is a new type of board that is currently attracting much attention.

[0003] The formula and process for preparing inorganic plywood based on magnesium oxide cement are becoming increasingly mature. Using magnesium oxide cement as an inorganic adhesive has excellent properties such as formaldehyde-free, good bonding strength, water resistance, and flame retardancy. However, it still has problems such as low viscosity, short open time, and easy moisture absorption, which leads to ion precipitation and corrosion of steel nails / keels.

[0004] In order to solve the above problems and make the performance of magnesium oxide cement close to that of existing urea glue, it is necessary to improve its performance technically. By technically modifying magnesium oxide cement in a low-cost manner to make it closer to the existing urea glue process and reduce adverse effects such as frosting and moisture absorption, the production efficiency of plywood can be truly improved. Summary of the Invention

[0005] To address the technical issues of existing magnesium oxide cement-based cold-pressed adhesives, such as low viscosity, short open time, and hygroscopic properties, and to achieve performance closer to that of existing urea-based adhesive systems, the inventors of this invention, building on their extensive research into inorganic adhesives, have developed a modified magnesium oxide cold-pressed adhesive and its preparation method. This modified magnesium oxide cold-pressed adhesive utilizes a cellulose-crosslinked polyacrylamide hydrogel network to form a liquid-phase adhesive component, creating a liquid-solid two-component adhesive system. This system is closer to existing urea-based adhesive-flour systems, improving bonding performance and open time while reducing adverse effects such as blooming and hygroscopicity.

[0006] The present invention specifically adopts the following technical solutions:

[0007] A modified magnesium oxide cold-pressed adhesive consists of a liquid-phase adhesive component and a solid-phase adhesive component stored separately; the liquid-phase adhesive component includes a cellulose-polyacrylamide hydrogel, an organic viscosity enhancer, and a soluble magnesium salt uniformly mixed in water, and the solid-phase adhesive component includes an inorganic mineral and magnesium oxide uniformly mixed.

[0008] The cellulose-polyacrylamide hydrogel is a homogeneous solution formed by uniformly mixing a cellulose solution and polyacrylamide.

[0009] Furthermore, the mass ratio of cellulose to dispersion water and polyacrylamide in the cellulose solution is 0.3-0.8:15-30:1.

[0010] Furthermore, the cellulose is selected from any one of nanocellulose, bacterial cellulose, hydroxypropyl methylcellulose, carboxymethyl cellulose, and ethyl cellulose, or a mixture of at least two of them in any proportion.

[0011] Furthermore, the molecular weight of polyacrylamide is 6 to 18 million.

[0012] The amount of polyacrylamide used is 2% to 10% of the mass of magnesium oxide.

[0013] The amount of the organic thickener used is 5% to 15% of the mass of the soluble magnesium salt.

[0014] Furthermore, the organic thickener is selected from any one of polyvinyl alcohol, polylactic acid, starch, sodium carboxymethyl cellulose, gelatin, or a mixture of at least two of them in any proportion.

[0015] The mass ratio of the soluble magnesium salt to water is 1:0.4-0.6. It should be noted that the "water" herein refers only to the water used to mix the cellulose-polyacrylamide hydrogel, the organic thickener, and the soluble magnesium salt in the liquid-phase adhesive component, and does not include the water used for dispersion when forming the cellulose solution in the cellulose-polyacrylamide hydrogel.

[0016] Furthermore, the soluble magnesium salt is selected from any one of magnesium chloride hexahydrate and magnesium sulfate heptahydrate, or a mixture of the two in any proportion.

[0017] The amount of inorganic mineral powder used is 5% to 10% of the mass of magnesium oxide.

[0018] Furthermore, the inorganic mineral powder is selected from any one of diatomaceous earth, silica fume, and silicon dioxide, or a mixture of at least two of them in any proportion.

[0019] The molar ratio of active magnesium oxide to soluble magnesium salt in the magnesium oxide is 5 to 9:1.

[0020] Furthermore, the magnesium oxide is light dead-burned magnesium oxide, and / or the mass content of active magnesium oxide therein is not less than 60%.

[0021] The present invention also discloses a method for preparing the modified magnesium oxide cold-pressed adhesive, comprising the following steps:

[0022] S1, preparation of cellulose-polyacrylamide hydrogel;

[0023] The cellulose is fully dispersed in water, and polyacrylamide is added to the obtained cellulose solution, and stirred until a homogeneous solution is obtained to obtain a cellulose-polyacrylamide hydrogel;

[0024] S2. Preparation of liquid phase bonding components;

[0025] Disperse the organic thickener thoroughly in water, add soluble magnesium salt, and stir until a homogeneous solution is obtained;

[0026] uniformly mixing the cellulose-polyacrylamide hydrogel with the obtained homogeneous solution containing the organic viscosity enhancer to obtain a liquid-phase adhesive component;

[0027] S3, preparation of solid phase bonding components;

[0028] The inorganic minerals and magnesium oxide are mixed uniformly to obtain a solid phase cementing component;

[0029] S4. Storing the liquid-phase adhesive component and the solid-phase adhesive component separately to obtain a modified magnesium oxide cold-pressed adhesive.

[0030] Generally, in step S1, in order to fully disperse cellulose in water, the mixed system of cellulose and water can be heated to 60° C. to 80° C. for dispersion, and after cooling to room temperature, polyacrylamide is added to the obtained cellulose solution.

[0031] The modified magnesium oxide cold-pressed adhesive provided by the present invention is based on the basic components of the existing magnesium oxide adhesive. First, a specially formed cellulose-polyacrylamide hydrogel is added. First, a hydrogel network constructed by cellulose cross-linked polyacrylamide is formed with the magnesium oxide adhesive basic system to form an interpenetrating network. The hydrogel network in the interpenetrating network ensures the stability of the liquid-phase adhesive component in the cold-pressed adhesive and improves the viscosity, density and fluidity of the inorganic gelling system (i.e., the magnesium oxide adhesive basic system); accordingly, the inorganic gelling system is filled in the hydrogel network, which ensures the coating thickness and mechanical properties of the adhesive layer and reduces the permeability of the hydrogel network; the construction of the interpenetrating network ensures that the cold-pressed adhesive has an excellent bonding effect when applied to wood, and the obtained adhesive layer has good heat resistance and water resistance. Secondly, the cellulose-polyacrylamide hydrogel's excellent water retention significantly increases the open time of the inorganic gelling system, meeting the time requirements of processes such as sizing and assembly. Furthermore, the temperature-sensitive cellulose-polyacrylamide hydrogel shrinks and loses water as the inorganic gelling system reacts. While releasing water to promote the hydration of magnesium oxide cement, the shrinkage of the polymer hydrogel network also increases the resistance to ion migration, acting as an ion anchor, thereby reducing adverse effects such as blooming and moisture absorption, and preventing free ions in the glue from corroding metal structures such as keels during application. The addition of cellulose allows its hydroxyl groups to form intermolecular hydrogen bonds with the carbonyl and amine groups of polyacrylamide, improving the stability of the polyacrylamide network and, in turn, the stability of the liquid phase.

[0032] Secondly, the compound use of organic thickeners can, on the one hand, improve the stability of the cellulose-polyacrylamide hydrogel network, and on the other hand, the active functional groups on it can chemically bond with the inorganic gelling system, so that the hydration products of magnesium cement therein overlap and intersect, and the structure is denser, thereby improving the water resistance (i.e., bonding strength) of the plywood based on it.

[0033] Thirdly, the addition of inorganic mineral powder, when applied, can, on the one hand, improve the coating performance of the modified magnesium oxide cold-pressed adhesive and achieve uniform coating of the adhesive layer; on the other hand, it can fill the adhesive layer, increasing the density of the adhesive layer and further improving the water resistance (i.e., bonding strength) of the plywood based on it. In addition, the inorganic mineral powder has a small specific surface area and can play a role similar to that of a "ball", making it more suitable for the roller coating process of the cold-pressed adhesive and avoiding the problem of "regeneration" of the flour.

[0034] Finally, the modified magnesium oxide cold-pressed adhesive is formulated into two parts: a liquid-phase adhesive component and a solid-phase adhesive component that are stored independently. This configuration is similar to the existing combination of urea glue and flour in current plywood factories, which meets the needs of long-distance transportation and long-term storage of glue. When needed, the two can be simply mixed and stirred evenly, which greatly reduces the threshold for using glue and is more conducive to the vigorous promotion and application of magnesium oxide-based adhesives.

[0035] Based on the modified magnesium oxide cold-pressed adhesive, the present invention further provides a flame-retardant plywood, which is obtained by applying the modified magnesium oxide cold-pressed adhesive to veneers and then assembling, cold pressing, drying, and curing.

[0036] Among them, the sizing amount of modified magnesium oxide cold pressing adhesive is 330g / m 2 ~440g / m 2 .

[0037] Among them, the cold pressing process has a unit pressure of 1.0MPa to 1.5MPa, and the cold pressing time is 12h to 24h.

[0038] A process for producing flame-retardant plywood comprises the following steps:

[0039] Q1, the above modified magnesium oxide cold pressing adhesive is prepared according to 330g / m 2 ~440g / m 2 Apply glue to the surface of the veneer;

[0040] Q2. Assemble the veneers after gluing in an orthogonal manner;

[0041] Q3. Cold pressing the green body obtained by the assembly under a pressure of 1.0 MPa to 1.5 MPa per unit area for 12 to 24 hours to obtain a formed plate;

[0042] Q4. Dry and cure the formed board to obtain flame-retardant plywood.

[0043] Generally, in step Q4, the drying temperature is 50° C. to 70° C., the drying time is 12 h to 60 h, and the curing time is 3 d to 7 d. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a comparison chart of the stability of the liquid phase components in the magnesium oxide cold-pressed adhesive provided by Example 3 of the present invention and Comparative Example 1 after aging for 2 days. DETAILED DESCRIPTION

[0045] The following will describe the modified magnesium oxide cold-pressed adhesive and its preparation method provided by the present invention, as well as the flame-retardant plywood based on the modified magnesium oxide cold-pressed adhesive and its production method through specific examples. However, those skilled in the art will understand that the following embodiments are only specific examples of the present invention and are not intended to limit the entire invention. Instead, these embodiments are provided to explain the principles of the present invention and its practical applications, so that other persons skilled in the art can understand the various embodiments of the present invention and various modifications suitable for specific intended applications.

[0046] Example 1

[0047] This embodiment provides a modified magnesium oxide cold-pressed adhesive and a preparation method thereof.

[0048] First, weigh 0.3 kg of ethyl cellulose, mix it with 15 kg of water, and disperse it with a high-speed disperser at 60°C to obtain a cellulose solution; after cooling to room temperature, add 1 kg of polyacrylamide (molecular weight of 6 to 9 million) and stir it at a low speed to obtain a cellulose-polyacrylamide hydrogel for standby use.

[0049] Then, 0.9 kg of polyvinyl alcohol was weighed and dissolved in 6.8 kg of water, and 17 kg of magnesium chloride hexahydrate was added thereto and stirred until a homogeneous solution was formed. Then, the above-mentioned cellulose-polyacrylamide hydrogel was added to the obtained homogeneous solution and stirred evenly to obtain a liquid-phase adhesive component.

[0050] Next, 50 kg of magnesium oxide (with an active magnesium oxide content of 60 wt%) and 2.5 kg of diatomaceous earth were weighed and mixed uniformly to obtain a solid-phase bonding component.

[0051] Finally, the liquid-phase adhesive component and the solid-phase adhesive component are stored separately to obtain the modified magnesium oxide cold-pressed adhesive.

[0052] When the modified magnesium oxide cold-pressed adhesive is to be used, the liquid-phase adhesive component and the solid-phase adhesive component are fully and evenly stirred, and then adhesive application is performed.

[0053] The modified magnesium oxide cold-pressed adhesive consists of a liquid-phase adhesive component and a solid-phase adhesive component. The liquid-phase adhesive component includes a cellulose-polyacrylamide hydrogel (formed by uniformly dispersing 0.3kg of ethyl cellulose, 15kg of water, and 1kg of polyacrylamide), 0.9kg of polyvinyl alcohol, and 17kg of magnesium chloride hexahydrate, all mixed in 6.8kg of water. The solid-phase adhesive component includes a uniform mixture of 2.5kg of diatomaceous earth and 50kg of magnesium oxide.

[0054] Example 2

[0055] This embodiment provides a modified magnesium oxide cold-pressed adhesive and a preparation method thereof.

[0056] First, weigh 8 kg of carboxymethyl cellulose, mix it with 300 kg of water, and disperse it with a high-speed disperser at 80°C to obtain a cellulose solution; after cooling to room temperature, add 10 kg of polyacrylamide (molecular weight of 9 to 12 million) and stir it at a low speed to obtain a cellulose-polyacrylamide hydrogel for standby use.

[0057] Then, 10 kg of starch was weighed and dissolved in 39.8 kg of water, and 36.8 kg of magnesium sulfate heptahydrate and 29.8 kg of magnesium chloride hexahydrate were added thereto, and stirred until a homogeneous solution was formed; then, the above-mentioned cellulose-polyacrylamide hydrogel was added to the obtained homogeneous solution, and stirred evenly to obtain a liquid-phase adhesive component.

[0058] Next, 100 kg of magnesium oxide (with an active magnesium oxide content of 60 wt%) and 10 kg of diatomaceous earth were weighed and mixed uniformly to obtain a solid-phase bonding component.

[0059] Finally, the liquid-phase adhesive component and the solid-phase adhesive component are stored separately to obtain the modified magnesium oxide cold-pressed adhesive.

[0060] When the modified magnesium oxide cold-pressed adhesive is to be used, the liquid-phase adhesive component and the solid-phase adhesive component are fully and evenly stirred, and then adhesive application is performed.

[0061] In other words, the modified magnesium oxide cold-pressed adhesive consists of a liquid-phase adhesive component and a solid-phase adhesive component. The liquid-phase adhesive component includes a cellulose-polyacrylamide hydrogel (8kg of carboxymethyl cellulose, 300kg of water, and 10kg of polyacrylamide uniformly dispersed in 39.8kg of water), 10kg of starch, 36.8kg of magnesium sulfate heptahydrate, and 29.8kg of magnesium chloride hexahydrate, all mixed uniformly in 39.8kg of water. The solid-phase adhesive component includes 10kg of diatomaceous earth and 100kg of magnesium oxide, all mixed uniformly.

[0062] Example 3

[0063] This embodiment provides a modified magnesium oxide cold-pressed adhesive and a preparation method thereof.

[0064] First, 4 kg of nanocellulose was weighed, mixed with 200 kg of water, and dispersed by stirring in a high-speed disperser at 80°C to obtain a cellulose solution; after cooling to room temperature, 8 kg of polyacrylamide (molecular weight of 12 to 18 million) was added thereto, and after stirring at a low speed, a cellulose-polyacrylamide hydrogel was obtained for standby use.

[0065] Then, 3.2 kg of gelatin was weighed and dissolved in 20 kg of water, and 40 kg of magnesium chloride hexahydrate was added thereto and stirred until a homogeneous solution was formed. Then, the above-mentioned cellulose-polyacrylamide hydrogel was added to the obtained homogeneous solution and stirred evenly to obtain a liquid-phase adhesive component.

[0066] Next, 80 kg of magnesium oxide (with an active magnesium oxide content of 60 wt%) and 6.4 kg of silica fume were weighed and mixed uniformly to obtain a solid-phase bonding component.

[0067] Finally, the liquid-phase adhesive component and the solid-phase adhesive component are stored separately to obtain the modified magnesium oxide cold-pressed adhesive.

[0068] When the modified magnesium oxide cold-pressed adhesive is to be used, the liquid-phase adhesive component and the solid-phase adhesive component are fully and evenly stirred, and then adhesive application is performed.

[0069] The modified magnesium oxide cold-pressed adhesive consists of a liquid-phase adhesive component and a solid-phase adhesive component. The liquid-phase adhesive component includes a cellulose-polyacrylamide hydrogel (formed by uniformly dispersing 4kg of nanocellulose, 200kg of water, and 8kg of polyacrylamide), 3.2kg of gelatin, and 40kg of magnesium chloride hexahydrate, all mixed in 20kg of water. The solid-phase adhesive component includes a uniform mixture of 6.4kg of silica fume and 80kg of magnesium oxide.

[0070] In order to demonstrate the necessity of each component in the modified magnesium oxide cold-pressed adhesive provided by the above embodiments of the present invention, several comparative experiments were conducted.

[0071] Comparative Example 1

[0072] The similarities between this comparative example and Example 3 are not repeated here, and only the differences from Example 3 are described. The comparative cold-pressed adhesive provided in this comparative example differs from the modified magnesium oxide cold-pressed adhesive in Example 3 in terms of components and preparation method in that the liquid-phase adhesive component does not contain cellulose-polyacrylamide hydrogel. That is, only a homogeneous solution of equal masses of gelatin, water, and magnesium chloride hexahydrate is used as the comparative liquid-phase adhesive component; otherwise, the comparative cold-pressed adhesive is provided with reference to Example 3.

[0073] The liquid phase adhesive components in Example 3 and Comparative Example 1 were aged for 2 days, and the physical stability comparison diagram is shown in FIG. Figure 1 As shown. Figure 1 , the container marked with serial number ① on the left represents the liquid-phase adhesive component in Example 3, and the container marked with serial number ② on the right represents the comparative liquid-phase adhesive component in Comparative Example 1.

[0074] from Figure 1 As can be seen, the liquid-phase adhesive component in Example 3 remained homogeneous, while the liquid-phase adhesive component in Comparative Example 1, lacking the cellulose-polyacrylamide hydrogel, exhibited significant stratification after only two days of aging, indicating that the liquid-phase adhesive component was unstable. This suggests that the cellulose-polyacrylamide hydrogel plays an important role in the stability of the liquid-phase adhesive component.

[0075] Comparative Example 2

[0076] The similarities between this comparative example and Example 3 are not repeated here, and only the differences from Example 3 are described. The comparative cold-pressed adhesive provided in this comparative example differs from the modified magnesium oxide cold-pressed adhesive in Example 3 in terms of components and preparation method in that the liquid-phase adhesive component does not contain gelatin used to modify magnesium chloride. That is, only a homogeneous solution of equal masses of cellulose-polyacrylamide hydrogel, water, and magnesium chloride hexahydrate is used as the comparative liquid-phase adhesive component; otherwise, the comparative cold-pressed adhesive is provided with reference to Example 3.

[0077] Comparative Example 3

[0078] The similarities between this comparative example and Example 3 are not repeated here, and only the differences from Example 3 are described. The comparative cold-pressed adhesive provided in this comparative example differs from the modified magnesium oxide cold-pressed adhesive in Example 3 in terms of components and preparation method in that the solid-phase adhesive component does not contain silica fume, that is, only an equal mass of magnesium oxide is used as the comparative solid-phase adhesive component; otherwise, the comparative cold-pressed adhesive is provided with reference to Example 3.

[0079] Comparative Example 4

[0080] This comparative example uses the same amount of raw material components as in Example 3, except that the preparation process of the cold-pressed adhesive is as follows: 8 kg of polyacrylamide (molecular weight 12 to 18 million) and 200 kg of water are weighed and stirred evenly, 40 kg of magnesium chloride hexahydrate is added, and after stirring to dissolve, 3.2 kg of gelatin and 20 kg of water are added and stirred evenly to obtain a liquid colloidal component.

[0081] 80 kg of magnesium oxide (with an active magnesium oxide content of 60 wt %), 6.4 kg of silica fume and 4 kg of nanocellulose were weighed and mixed uniformly to obtain a solid-phase bonding component.

[0082] Finally, the liquid-phase adhesive component and the solid-phase adhesive component are stored separately to obtain comparative cold-pressed adhesive.

[0083] That is, in the preparation of the comparative cold-pressed glue, polyacrylamide and cellulose are mainly added separately, and the two come into contact only when the solid and liquid colloidal components are mixed during the application of the glue, rather than the two first coming into contact and reacting to form a cellulose-polyacrylamide hydrogel.

[0084] The viscosity, stability and open time of the magnesium oxide cold-pressed adhesive provided in the above embodiments and comparative examples of the present invention are shown in Table 1 below.

[0085] The viscosity is measured at 25°C using an NDJ-79 rotational viscometer. The stability test measures the delamination of the liquid adhesive components in each glue after standing for 48 hours. The open time is the time from the completion of coating to the complete drying of the glue after each cold-pressed adhesive is applied to the surface of the veneer (coating amount is 20g / 30cm*30cm).

[0086] Table 1 Performance results of magnesium oxide cold pressed adhesive provided in each embodiment and comparative example

[0087]

[0088] As can be seen from Table 1, the open time of the modified magnesium oxide cold-pressed adhesive provided by each embodiment of the present invention is greater than 3 hours, and the liquid phase adhesive component does not delaminate, the adhesive viscosity is high, and it meets the existing roller glue process.

[0089] In contrast, in Comparative Example 1, the lack of a cellulose-polyacrylamide hydrogel network shortened the cold-pressed adhesive's open time to 2 hours, significantly reducing the adhesive's viscosity and making it difficult to meet existing roller-bonding requirements. In Comparative Example 2, the lack of a soluble magnesium source modified with an organic thickener resulted in some stratification of the liquid phase component, and a decrease in viscosity. This is because, on the one hand, the addition of an organic thickener improves the stability of the cellulose-polyacrylamide hydrogel network, thereby improving the stratification of the liquid phase component. It also chemically bonds with magnesium oxide cement, improving the density of the adhesive layer. In Comparative Example 3, the lack of inorganic mineral powder had no significant impact on the directly measured properties of the cold-pressed adhesive. In Comparative Example 4, polyacrylamide and cellulose, respectively, are present in the liquid and solid phases of the adhesive. Both possess good water-retention properties, resulting in an excessively long open time and impacting the adhesive's drying rate. Furthermore, since the two components are stored separately and only come into contact during application, the high concentration of ions in the colloid hinders the formation of a hydrogel network, resulting in a decrease in the adhesive's viscosity and a failure to achieve a thickening effect.

[0090] Based on the modified magnesium oxide cold-pressed adhesive provided in the above embodiment, the present invention also produces flame-retardant plywood.

[0091] Example 4

[0092] This embodiment is based on the modified magnesium oxide cold-pressed adhesive provided in the above embodiment 1, and a flame-retardant plywood is produced according to the following process.

[0093] First, the liquid phase adhesive component and the liquid phase adhesive component in the modified magnesium oxide cold pressing adhesive are mixed evenly, and the mixture is heated to 330 g / m 2 The cold pressed glue is applied to the veneer layer by layer according to the amount of glue applied; and the veneers after gluing are assembled in an orthogonal manner.

[0094] Then, the green body obtained by the assembly was cold pressed at a unit pressure of 1.5 MPa for 12 hours, dried at 50°C for 60 hours, and cured for 3 days. The board surface was repaired, sanded and cut to obtain the inorganic flame-retardant multilayer plywood.

[0095] Example 5

[0096] This embodiment is based on the modified magnesium oxide cold-pressed adhesive provided in the above embodiment 2, and a flame-retardant plywood is produced according to the following process.

[0097] First, the liquid phase adhesive component and the liquid phase adhesive component in the modified magnesium oxide cold pressing adhesive are mixed evenly, and the mixture is heated to 440 g / m 2 The cold pressed glue is applied to the veneer layer by layer according to the amount of glue applied; and the veneers after gluing are assembled in an orthogonal manner.

[0098] Then, the green body obtained by the assembly was cold pressed at a unit pressure of 1.0 MPa for 24 hours, dried at 70°C for 12 hours, and cured for 7 days. The board surface was repaired, sanded and cut to obtain an inorganic flame-retardant multilayer plywood.

[0099] Example 6

[0100] This embodiment is based on the modified magnesium oxide cold-pressed adhesive provided in the above embodiment 3, and a flame-retardant plywood is produced according to the following process.

[0101] First, the liquid phase adhesive component and the liquid phase adhesive component in the modified magnesium oxide cold pressing adhesive are mixed evenly, and the mixture is heated to 400 g / m 2 The cold pressed glue is applied to the veneer layer by layer according to the amount of glue applied; and the veneers after gluing are assembled in an orthogonal manner.

[0102] Then, the green body obtained by the assembly was cold pressed at a unit pressure of 1.2 MPa for 18 hours, dried at 60°C for 36 hours, and cured for 5 days. The board surface was repaired, sanded and cut to obtain an inorganic flame-retardant multilayer plywood.

[0103] In order to further verify the performance of the comparative cold-pressed adhesives provided in the above comparative examples in plywood, comparative plywood was produced based on the comparative cold-pressed adhesives provided in the above comparative examples using the same production process as in Example 6.

[0104] Comparative Example 5

[0105] The similarities between this comparative example and Example 6 are not repeated here, and only the differences from Example 6 are described. This comparative example differs from Example 6 in that the modified magnesium oxide cold-pressed adhesive in Example 3 is replaced with the comparative cold-pressed adhesive in Comparative Example 1; otherwise, reference is made to Example 6, providing a comparative plywood.

[0106] Comparative Example 6

[0107] The similarities between this comparative example and Example 6 are not repeated here, and only the differences from Example 6 are described. This comparative example differs from Example 6 in that the modified magnesium oxide cold-pressed adhesive in Example 3 is replaced with the comparative cold-pressed adhesive in Comparative Example 2; otherwise, reference is made to Example 6, providing a comparative plywood.

[0108] Comparative Example 7

[0109] The similarities between this comparative example and Example 6 are not repeated here, and only the differences from Example 6 are described. This comparative example differs from Example 6 in that the modified magnesium oxide cold-pressed adhesive in Example 3 is replaced with the comparative cold-pressed adhesive in Comparative Example 3; otherwise, reference is made to Example 6, and a comparative plywood is provided.

[0110] Comparative Example 8

[0111] The similarities between this comparative example and Example 6 are not repeated here, and only the differences from Example 6 are described. This comparative example differs from Example 6 in that the modified magnesium oxide cold-pressed adhesive in Example 6 is replaced with the comparative cold-pressed adhesive in Comparative Example 4; otherwise, reference is made to Example 6, and a comparative plywood is provided.

[0112] The bonding strength and corrosion resistance of the plywood provided in Examples 4 to 6 and Comparative Examples 5 to 8 were tested, as shown in Table 2 below.

[0113] Among them, the bonding strength is tested in accordance with the provisions of GB / T 18101-2013 "Flame-retardant Plywood"; the corrosion resistance grading is tested in accordance with the provisions of Q / QNZ 035-2022 "Corrosion Resistance Grading of Flame-retardant Oriented Strand Board".

[0114] Table 2 Performance results of plywood provided in various embodiments and comparative examples

[0115]

[0116] As can be seen from Table 2, the plywood provided by each embodiment of the present invention has excellent bonding strength and corrosion resistance as high as level 5, which is mainly due to the excellent performance of the modified magnesium oxide cold-pressed adhesive provided in Examples 1 to 3.

[0117] In contrast, in Comparative Example 5, which uses a cold-pressed adhesive lacking cellulose-polyacrylamide hydrogel, the performance data for Comparative Example 1 in Table 1 show that the viscosity of the adhesive significantly decreases, affecting the amount of glue applied during roller coating. This results in a significant decrease in both the bonding strength and corrosion resistance of the resulting plywood. This is because the cellulose-polyacrylamide hydrogel network has excellent viscosity-enhancing properties and effectively fixes the free ions in the magnesium oxide cement, thereby reducing the corrosive effects of these free ions on the keel and self-tapping screws.

[0118] In Comparative Example 6, a cold-pressed adhesive lacking an organic tackifier was used. Combined with the performance data of Comparative Example 2 in Table 1, the lack of an organic tackifier resulted in a significant decrease in the viscosity of the cold-pressed adhesive, which in turn significantly reduced the bonding strength of the resulting plywood. Furthermore, the lack of chemical bonding between the cold-pressed adhesive and the magnesium cement hydration product also resulted in poor density of the adhesive layer, making it more susceptible to ion migration and deterioration of corrosion resistance.

[0119] Comparative Example 7, which uses cold-pressed adhesive lacking inorganic mineral powder, shows no significant degradation in the various directly measured data for the cold-pressed adhesive in Table 1. However, when used in plywood production, it still exhibits a trend of performance degradation. Specifically, both bond strength and corrosion resistance decrease. This is because the inorganic mineral powder not only increases the density of the adhesive layer, thereby improving the plywood's water resistance, but also enhances the adhesive application, facilitating uniform application.

[0120] In Comparative Example 8, after polyacrylamide and cellulose were added separately, it was difficult to form a hydrogel network, and a continuous network structure could not be formed in the glue. The viscosity of the glue decreased, and the adhesion to the surface of the veneer also decreased. At the same time, during the glue preparation process, due to the water absorption reaction of magnesium oxide, it formed a competitive relationship with the water used to dissolve cellulose, resulting in part of the cellulose being unable to be evenly dispersed, and obvious particles were present in the glue, affecting the bonding performance and ultimately leading to a significant reduction in the bonding strength. The inability of cellulose and polyacrylamide to form a network structure also led to the migration of free ions, resulting in a significant deterioration in corrosion resistance.

[0121] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. A modified magnesium oxide cold-pressed adhesive, characterized in that: It consists of a liquid-phase adhesive component and a solid-phase adhesive component stored separately; wherein the liquid-phase adhesive component includes cellulose-polyacrylamide hydrogel, an organic viscosity enhancer and a soluble magnesium salt uniformly mixed in water, and the solid-phase adhesive component includes inorganic minerals and magnesium oxide uniformly mixed.

2. The modified magnesium oxide cold-pressed adhesive according to claim 1, characterized in that: The cellulose-polyacrylamide hydrogel is a homogeneous solution formed by uniformly mixing a cellulose solution and polyacrylamide.

3. The modified magnesium oxide cold-pressed adhesive according to claim 2, characterized in that: The mass ratio of cellulose in the cellulose solution to the dispersion water and the polyacrylamide is 0.3-0.8:15-30:

1.

4. The modified magnesium oxide cold-pressed adhesive according to claim 3, characterized in that: The amount of the polyacrylamide is 2% to 10% of the mass of the magnesium oxide; the amount of the organic viscosity enhancer is 5% to 15% of the mass of the soluble magnesium salt; in the liquid phase bonding component, the mass ratio of the soluble magnesium salt to the water is 1:0.4 to 0.6; the amount of the inorganic mineral powder is 5% to 10% of the mass of the magnesium oxide; the amount of active magnesium oxide in the magnesium oxide to the soluble magnesium salt is 5 to 9:

1.

5. The modified magnesium oxide cold-pressed adhesive according to claim 4, characterized in that: The molecular weight of the polyacrylamide is 6 to 18 million.

6. The modified magnesium oxide cold-pressed adhesive according to any one of claims 1 to 5, characterized in that: The organic thickener is selected from any one of polyvinyl alcohol, polylactic acid, starch, sodium carboxymethyl cellulose, and gelatin, or a mixture of at least two of them in any proportion; the inorganic mineral powder is selected from any one of diatomaceous earth, silica fume, and silicon dioxide, or a mixture of at least two of them in any proportion; the soluble magnesium salt is selected from any one of magnesium chloride hexahydrate and magnesium sulfate heptahydrate, or a mixture of the two in any proportion.

7. The modified magnesium oxide cold-pressed adhesive according to claim 4, characterized in that: The magnesium oxide is light dead-burned magnesium oxide, and / or the mass content of active magnesium oxide in the magnesium oxide is not less than 60%.

8. The method for preparing the modified magnesium oxide cold-pressed adhesive according to any one of claims 1 to 7, characterized in that: Includes steps: S1, preparation of cellulose-polyacrylamide hydrogel; Fully dispersing cellulose in water, adding polyacrylamide to the obtained cellulose solution, and stirring to a homogeneous solution to obtain the cellulose-polyacrylamide hydrogel; S2. Preparation of liquid phase bonding components; The organic thickener is fully dispersed in water, and a soluble magnesium salt is added, and stirred to a homogeneous solution; the cellulose-polyacrylamide hydrogel and the obtained homogeneous solution containing the organic thickener are then mixed evenly to obtain the liquid-phase adhesive component; S3, preparation of solid phase bonding components; Mixing the inorganic mineral and magnesium oxide uniformly to obtain the solid phase bonding component; S4. Storing the liquid-phase adhesive component and the solid-phase adhesive component separately to obtain the modified magnesium oxide cold-pressed adhesive.

9. A flame retardant plywood, characterized in that: The modified magnesium oxide cold-pressed adhesive as claimed in any one of claims 1 to 7 is applied to a single board, and the process includes assembling, cold pressing, drying and curing.

10. The method for manufacturing a flame retardant plywood according to claim 9, characterized in that: Includes steps: Q1. The modified magnesium oxide cold-pressed adhesive according to any one of claims 1 to 7 is prepared at 330 g / m 2 ~440g / m 2 Apply glue to the surface of the veneer; Q2. Assemble the veneers after gluing in an orthogonal manner; Q3. Cold press the green body obtained by green assembly at a pressure of 1.0 MPa to 1.5 MPa per unit area for 12 to 24 hours to obtain a formed plate; Q4. Drying and curing the formed board to obtain the flame-retardant plywood.